Wybory Rady Nieustającej na sejmie 1778 roku - Filipczak, Witold (Acta Universitatis Lodziensis. Folia Historica, 1999)
Secret negotiations in the Sejm concerning the composition of the Council are discussed in the article. Special attention is paid to the changes in Russian policy towards Poland, connected with the war over succession to the throne in Bavaria. Policy of king Stanislaw August as well as activity of A. Tyzenhauz, the leader of the royal camp in Lithuania, were criticized by Stackelberg, Russian ambassador in Poland. In order to allay Russian misgivings, the king gave up preparing the list of candidates he supported. Then, the elections to the Council are discussed as well as their compliance with the law. The elections were successful for the Opposition, supported by Stackelberg. As a result they reduced their critical views of the Council. The king tried to be more independent in his political moves. Apparently he gave up policy of a secret control over the Sejm. Criticized by Stackelberg, he replied he had lost his control over his supporters.